2017
DOI: 10.1590/1516-3180.2016.008607072016
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary fatty acid intake in inflammatory gene expression: a critical review

Abstract: CONTEXT AND OBJECTIVE: Diet is an important modifiable factor involved in obesity-induced inflammation. We reviewed clinical trials that assessed the effect of consumption of different fatty acids on the expression of inflammation-related genes, such as cytokines, adipokines, chemokines and transcription factors. DESIGN AND SETTING: Narrative review study conducted at a research center. METHODS:This was a review on the effect of fat intake on inflammatory gene expression in humans. RESULTS: Consumption of satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 77 publications
(150 reference statements)
0
43
1
2
Order By: Relevance
“…A high SFA intake has been associated with proinflammatory response and gene regulation involved in inflammatory pathways, such as TNF-a, in adipose tissue. 59,60 In contrast, we observed a reduction in the amount of adiponectin messenger RNA (mRNA) expression, with increasing adipocyte size when VCO was combined with HFD. These results evidence that VCO when associated with HFD induces low-grade inflammation in adipose tissue, altering cytokines production, increasing proinflammatory and reducing anti-inflammatory markers.…”
mentioning
confidence: 73%
“…A high SFA intake has been associated with proinflammatory response and gene regulation involved in inflammatory pathways, such as TNF-a, in adipose tissue. 59,60 In contrast, we observed a reduction in the amount of adiponectin messenger RNA (mRNA) expression, with increasing adipocyte size when VCO was combined with HFD. These results evidence that VCO when associated with HFD induces low-grade inflammation in adipose tissue, altering cytokines production, increasing proinflammatory and reducing anti-inflammatory markers.…”
mentioning
confidence: 73%
“…Hydrogenated fats, ingredients commonly used in ultra-processed foods, have been identified as responsible for an increase in the inflammatory state of the body, via stimulating the activity of prostaglandin E2 and inhibiting anti-inflammatory agents, such as prostaglandins E1 and E3. It is known that prostaglandin E2 acts at birth by inducing uterine contraction 36,37 , which would favor early labor, prematurity and consequently low birth weight in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The type of FA stored in AT, besides adipocyte fat overload, critically affects tissue functions. FA can directly or indirectly modify immune and inflammatory responses by several mechanisms, acting on cell surface and intracellular receptors that control cell signaling and gene expression [12,13] . Recent studies have indicated that dietary FA quality rather than quantity has major implications in meta-inflammation development.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that dietary FA quality rather than quantity has major implications in meta-inflammation development. In fact, FA exhibit either pro-or anti-inflammatory activity depending on their chemical structure [11,13] . In general, long-chain SFA have been associated with inflammation while short-chain FA show anti-inflammatory effects [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation